Seismic risk assessment for historical town centers and their surroundings using geoinformatics: the case study of Paphos, Cyprus - Hadjimitsis, Diofantos G.; Agapiou, Athos; Chrysostomou, Christis; Kyriakides, Nicholas (My University, 2010)
This paper highlights the importance of using Remote Sensing and GIS for assisting the seismic risk assessment for historical town centres in Cyprus. The selected case study is the Paphos town centre including the archaeological area of Nea Paphos. The authors present their proposed methodology for inventory collection, which is based on the integrated use of aerial photos and satellite imagery and the application of digitisation process. A 3D representation of the area using the heights of the buildings and the orthophotos was produced in the ArcGIS software for a more realistic result. The information produced in this pilot project will be used for the seismic risk assessment of the case-study area
Keywords: Risk assessment; Land use; Remote sensing; Seismology; Signal detection